Pengaruh Penyertaan Modal Negara Terhadap Pembagian Dividen Pada BUMN: Peran Penugasan Sebagai Variabel Moderasi - Satrio, Aditya Agung; Olfah, Sumadiyah T.; Fardian, Fatkhi; Maulana, Ahmad (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2025)
This study examines the relationship between state equity participation (PMN) and dividend distribution in state-owned enterprises (SOEs), with government assignments serving as a moderating variable. PMN represents a crucial instrument utilized by the government to reinforce the capital base of SOEs. Although PMN is designed to enhance the financial performance of SOEs, its influence on dividend distribution remains unclear, particularly in the context of government assignments. This study employs panel data from 55 SOEs over the period 2010-2022. The analysis is conducted with quantitative methods, specifically panel data regression, to examine the relationship between PMN and dividends with assignment as a moderating variable. The findings indicate that the impact of PMN on SOE dividends varies depending on the time period under consideration. In the year of the PMN grant and the subsequent year, there is no statistically significant relationship between PMN and dividends. In the second year, there is a negative relationship between PMN and dividends; however, in the third year, the impact shifts to a significant positive. The findings of this study lend support to the hypothesis that PMN has the potential to increase dividends over the long term, despite the tendency for funds to be allocated to public assignments in the short term, which may result in a reduction in potential earnings. The findings also confirm that assignments play a significant moderating role initially, but diminish over time, suggesting the importance of policy adjustments regarding assignments and dividend targets. The policy implication of this study is that long-term planning is necessary to optimize the use of PMN, with a focus on financial stabilization and long-term investment for SOEs. The government should prioritize the acceleration of the disbursement process to enable SOEs to respond rapidly to market dynamics.